A new species of Prosopistoma (Ephemeroptera: Prosopistomatidae) from China with a key to Oriental species - Shi, Weifang; Tong, Xiaoli (Zootaxa, 2013)
A new species of the monogeneric family Prosopistomatidae, Prosopistoma ocellatum sp. n., is described and illustrated based on mature larval stages from Guangxi and Hainan, southern China. The new species can be readily distinguished from the other members of Prosopistoma by the following combination of characters: antenna 6-segmented, segment III much longer than segments IV–VI; three bristles at the base of the inner canine; 10–11 pectinate setae on ventral margin of fore tibiae, ventral and basal half surface of all femora with dense scale-like structures, and color pattern of eye-spot on the mesonotum. An update key to the known Oriental species is provided.